2021
DOI: 10.1111/pace.14137
|View full text |Cite
|
Sign up to set email alerts
|

No impact of mineralocorticoid receptor antagonists on long‐term recurrences of ventricular tachyarrhythmias

Abstract: Objective The study sought to assess the prognostic impact of treatment with mineralocorticoid receptor antagonists (MRA) on recurrences of ventricular tachyarrhythmias in implantable cardioverter‐defibrillator (ICD) recipients with systolic heart failure (HF). Background Data regarding the outcome of patients with ventricular tachyarrhythmias treated with MRA is limited. Methods A large retrospective registry was used including consecutive ICD recipients with systolic HF (i.e., left ventricular ejection fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Our working group recently found a treatment rate by MRA of only 20% in a real‐life cohort of consecutive implantable cardioverter defibrillator recipients and a history of ventricular tachyarrhythmias (left ventricular ejection fraction <35: 70%). 10 The prospective BioSTAT‐CHF (A Systems Biology Study to Tailored Treatment in Chronic Heart Failure) study revealed a MRA treatment rate of only 56% of 1,049 eligible patients suffering from systolic heart failure (ie, left ventricular ejection fraction <35%) and formal indication for MRA treatment (ie, estimated glomerular filtration rate ≥30 mL/min per 1.73 m 2 and potassium level ≤5.0 mmol/L). 11 Even the discontinuation of MRA therapy was reported in 16% of patients at 9 months, whereas a new initiation of MRA therapy was observed in only 36%.…”
mentioning
confidence: 99%
“…Our working group recently found a treatment rate by MRA of only 20% in a real‐life cohort of consecutive implantable cardioverter defibrillator recipients and a history of ventricular tachyarrhythmias (left ventricular ejection fraction <35: 70%). 10 The prospective BioSTAT‐CHF (A Systems Biology Study to Tailored Treatment in Chronic Heart Failure) study revealed a MRA treatment rate of only 56% of 1,049 eligible patients suffering from systolic heart failure (ie, left ventricular ejection fraction <35%) and formal indication for MRA treatment (ie, estimated glomerular filtration rate ≥30 mL/min per 1.73 m 2 and potassium level ≤5.0 mmol/L). 11 Even the discontinuation of MRA therapy was reported in 16% of patients at 9 months, whereas a new initiation of MRA therapy was observed in only 36%.…”
mentioning
confidence: 99%